THE ROLE OF THE INSTAGRAM ACCOUNT @INFODARJO IN THE DISSEMINATION OF LOCAL INFORMATION IN SIDOARJO - Kusuma, Bagas; Istiqomah (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research aims to understand the role of the Instagram account in spreading local information. Method: This study uses a descriptive qualitative method to analyze 'The Role of Instagram Account @infodarjo in the Dissemination of Local Information in Sidoarjo.' This research employs observation and account analysis as data collection techniques. Observations will be made by monitoring the activities that occur. Account analysis will be conducted by analyzing the activities carried out through the platform, from story posts, photo or video uploads on the account, to the responses received from social media users. Results: Based on the observations that have been made, this account actively shares information about current events, traffic, local events, and various public services. The speed and consistency in uploading information make it easier for the community to obtain the latest news compared to conventional media. Instagram accounts like @infodarjo serve as an alternative medium that is fast, interactive, and easily accessible to the public, especially the younger generation. The high level of user interaction indicates that this account is not only a medium for conveying information but also a platform for communication and discussion for the people of Sidoarjo. Novelty: Instagram accounts like @infodarjo serve as an alternative medium that is fast, interactive, and easily accessible to the public, especially the younger generation. The high level of user interaction indicates that this account is not only a medium for conveying information but also a platform for communication and discussion for the people of Sidoarjo.